W poszukiwaniu istoty nowego autorytarnego porządku. Antoniego Peretiatkowicza koncepcja cezaryzmu demokratycznego - Ławnikowicz, Grzegorz (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article’s aim is to reconstruct the concept of democratic Caesarism. It is an attempt to recreate, Antoni Peretiatkowicz’s ideas about the origin and the essence of Caesarisms.The delimitation of the boundaries of democratic Caesarism entailed the need for definition and critical analysis of the specific characteristics of this system. One of the main objectives of the research was the answer to the question of the reasonableness of Peretiatkowicz’s approach to old and modern (from his perspective) political regimes considered a single set and at the same time constituting separate systems: Spanish, Italian, German, Turkish and Polish. The answer to this question was facilitated by the definition of the relationship between the concepts of “Caesarism” and “authoritarianism”. The research has shown that the Poznań professor’s work was an attempt to build not only a certain objective description of the concept, but also to justify, become familiar with and nationalize the transformations taking place in Europe during the inter-war period, in particular in Poland.The deliberations also addressed the assessment of the maturity of the concept, in particular the degree of its realism and originality. The final part of the article points to the historical repeatability of the arguments aimed at rationalizing and legitimizing dictatorship (the concept of a transitional dictatorship, justification for enlightened absolutism).
Keywords: Peretiatkowicz, Antoni (1884-1956); democratic Caesarism; authoritarianism; totalitarianism; Second Polish Republic